Assessing development effectiveness : Evaluation in the World Bank and the International Finance Corporation - World Bank (Independent Evaluation Group Studies, 1994)
Effective management of development requires reliable feedback about the impact of ongoing and completed operations. This is the major goal of evaluation. Learning from development experiences calls for a well focused and well structured system of operations evaluation. The World Bank's operations evaluation organization has been in existence for more than two decades. It provides comprehensive information for management decisions at all levels and supports a continuing process of performance improvement. Closely linked to the project cycle and to policy reform, evaluation in the Bank incorporates contributions from borrowers, who are the owners of the operations that the Bank finances. Operations evaluation provides insights and recommendation of value to development practitioner both within and outside the Bank